Development of Interactive Learning Media in Information and Communication Technology (ICT) Class X IPA - Roni Ilham; Syahril syahril; Krimadinata Krimadinata (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
This research was about the media where the lack of availability of learning facilities caused students to not be able to master the subject matter so that students' low skills affect their learning outcomes. The purpose of this study was to produce interactive learning media on the subject of Information and Communication Technology (ICT) in class X MAN which was valid, practice and effective so that it can assist teachers in delivering material more creatively and innovatively, and help students master the subject matter. This type of research was research and development (R &D). The development model used was a 4-D model which consisted of the stages of defining, designing, developing and disseminating. The define stage was carried out by curriculum analysis, material analysis, and student analysis. The design stage was carried out by designing the learning media. In the development stage, the validity test was carried out through the learning media validation sheet, the practicality test through the media implementation observation sheet, the teacher and student response questionnaires, the effectiveness test was obtained from the knowledge competency assessment. The dessiminate stage was carried out by deploying the devices. The data analysis used was the Cohen Kappa formula. Based on the analysis, it showed that the validity test in terms of media and interactive learning materials in the Information and Communication Technology subject had been tested and declared very valid, namely 0.90; the practicality test of the teacher's response were 0.79 in the practical category and 0.81 student's response was in the very practical category; The effectiveness of the experimental class on average learning outcomes was 84.52 while the control class averages 75.16 learning outcomes with this value interactive multimedia was categorized as a valid, practiced and effective and media used as a learning medium.